2014
DOI: 10.1021/nn502438k
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High-Quality Single-Atom Nitrogen Doping of Graphene/SiC(0001) by Ion Implantation and Subsequent Thermal Stabilization

Abstract: We report a straightforward method to produce high-quality nitrogen-doped graphene on SiC(0001) using direct nitrogen ion implantation and subsequent stabilization at temperatures above 1300 K. We demonstrate that double defects, which comprise two nitrogen defects in a second-nearest-neighbor (meta) configuration, can be formed in a controlled way by adjusting the duration of bombardment. Two types of atomic contrast of single N defects are identified in scanning tunneling microscopy. We attribute the origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 33 publications
11
105
0
Order By: Relevance
“…9,10 Moreover, we find a strong increase for positive voltage indicating the onset of the nitrogen donor level. 9,26 Similarly, for the boron signature in Figure 3d a corresponding increase is found for negative bias voltages as expected for the boron acceptor level. 24 The total shape of the boron dopant spectrum fits theoretical predictions 26,27 of the LDOS including the increase in spectral weight at 1 eV that is depending on the interaction between neighboring sites.…”
supporting
confidence: 79%
“…9,10 Moreover, we find a strong increase for positive voltage indicating the onset of the nitrogen donor level. 9,26 Similarly, for the boron signature in Figure 3d a corresponding increase is found for negative bias voltages as expected for the boron acceptor level. 24 The total shape of the boron dopant spectrum fits theoretical predictions 26,27 of the LDOS including the increase in spectral weight at 1 eV that is depending on the interaction between neighboring sites.…”
supporting
confidence: 79%
“…From the AFM image, it is concluded that the feature observed in the STM channel is located at the top site of the moiré lattice. Previously, a very similar signature in STM images was attributed to two N atoms on neighboring positions on the same sublattice, i.e., with one N atom in the meta position with respect to the other [23]. Figures 6(g) and 6(h) show the f min and z min maps.…”
Section: Referencesupporting
confidence: 51%
“…A more zoomed view of such a graphene patch, Fig. 3(b), shows characteristic triangularshaped features that have been assigned to individual N dopants in graphene [23,25,45]. Determining the optimal parameters to grow large graphene flakes on Cu(111) using the method described above is beyond the scope of the present paper.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the B C intensity is constant, suggesting that the B atoms in the graphene and BL lattices are thermally stable. Unlike in N-doped graphene [27], there is only one local bonding configuration between the dopant and the host lattice, as evidenced by the single peak B C at 190.8 eV. Moreover, as no BE shift is observed for B C between 1050 and 1150…”
mentioning
confidence: 96%